Samarahan District Council - Jenal, Norfazila (Universiti Teknologi MARA, Sarawak, 2012)
Samarahan District Council is located in the Samarahan area about 30 kilometres from Kuching. SDC was gazetted on 27 December 1984 and perform the powers to administer the areas under his control begins on January 1, 1985. In addition, the areas under the control of the SDC are includes sub-district of Asajaya and Sadong Jaya. Chairman of the Council, and also known as Wali-city, led SDC based on the provisions of the Ordinance, the powers of the Local (The Local Authority Ordinance). SDC has an area of 593.9 square kilometres. According to the 2000 Population Census, the total population of the District Samarahan is (46.966) and Asajaya (28.513) is 75, 476. Other than that, the appearance of the terrain is flat and Samarahan District consists primarily of lowland or peat. Because of this situation, these lands are suitable for farming activities which had been conducted by IADA. Among the produced commodity are citrus plants, coconut, oil palm and pineapple. There are also a popular cash crop paddy rice, melons, sweet corn and vegetables.